The effects of water depth on the growth and reproduction of Potamogeton crispus in an in situ experiment. (23rd May 2016) - Zhou, Nannan; Hu, Weiping; Deng, Jiancai; Zhu, Jinge; Xu, Weiwei; Liu, Xin
Abstract: Aims: Water level is one of the most important determinants of the distribution and composition of submersed aquatic vegetation in shallow lakes. Without changes in nutrient loading, large-scale declines in submerged macrophytes in shallow lakes are largely attributed to strong external or internal forces, including changes in water level. As a winter-active submerged macrophyte, Potamogeton crispus has important functions in aquatic ecosystem. The objectives of our study were to reveal the effects of water depths on the germination, growth, reproduction and morphological changes of P. crispus under natural environmental conditions; identify the optimum water depth range for colonization of P. crispus ; and predict the succession course for P. crispus in Lake Taihu. Methods: A long-term in situ experiment was performed to study the effects of water depth on the growth and morphology of P. crispus across the entire life cycle. Plants were grown in the improved cross type of rhizotrons for 30 weeks at three different water depths (60, 120 and 200cm) in Dongtaihu Bay of Lake Taihu. We measured the plant height, root length, the length and width of leaves and counted the numbers of leaves, ramets, turion spikes and roots of each plant on each observation day during the experiment. Important Findings: Water depths ranging from 60 to 120cm were favourable for above-ground vegetation growth, root tissue growth and the reproductive ability of P. crispus . At water depth of 200cm or beyond, the distribution of P. crispus will be limited in the following year because of the lack of turion formation and the severe inhibition of ramet production. The relationship between above-ground biomass and growth time at three different water depths fits a logistic growth curve well ( P < 0.001). The rapid growth and distribution with high density of P. crispus at water depth near 60cm during the reproductive stage is not favourable for growth of other submerged species. So a continuous water depth of ~60–120cm is the optimum growth depth range for the conservation and restoration of P. crispus in Lake Taihu. In addition, the morphological parameters values acquired can replace or provide the ranges for the value of G maxSB (the maximum growth rate of submerged plants, in the unit of d −1 ) obtained via calibration in the control equations of submerged plant growth in the Eco-Taihu model, which is a three-dimensional ecological model of Lake Taihu.